Antibody Pharmacokinetics and Pharmacodynamics - Lobo, Evelyn D.; Hansen, Ryan J.; Balthasar, Joseph P. (Journal of pharmaceutical sciences, 2004)
The U.S. Food and Drug administration (FDA) has approved several polyclonal antibody preparations and at least 18 monoclonal antibody preparations (antibodies, antibody fragments, antibody fusion proteins, etc.). These drugs, which may be considered as a diverse group of therapeutic proteins, are associated with several interesting pharmacokinetic characteristics. Saturable binding with target antigen may influence antibody disposition, potentially leading to nonlinear distribution and elimination. Independent of antigen interaction, concentration‐dependent elimination may be expected for IgG antibodies, due to the influence of the Brambell receptor, FcRn, which protects IgG from catabolism. Antibody administration may induce the development of an endogenous antibody response, which may alter the pharmacokinetics of the therapeutic antibody. Additionally, the pharmacodynamics of antibodies are also complex; these drugs may be used for a wide array of therapeutic applications, and effects may be achieved by a variety of mechanisms. This article provides an overview of many of the complexities associated with antibody pharmacokinetics and pharmacodynamics. © 2004 Wiley-Liss, Inc. and the American Pharmacists Association J Pharm Sci 93:2645–2668, 2004